The Influence of Multinationality and Capital Intensity on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange - M. Alimuddin; Susi Sarumpaet (International Journal of Economics and Management Sciences, 2024)
This study analyzes the impact of multinationality and capital intensity on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the primary consumer goods sector for the period 2020-2022. Data was obtained through purposive sampling from the annual reports of these companies. The variables studied include multinationality, capital intensity, leverage, company size, and profitability. The results show that multinationality has a significant impact on tax avoidance, while capital intensity does not show a significant effect. Control variables such as leverage, company size, and profitability also have a significant impact on tax avoidance.